Types of Slang in Windah Basudara's Speech on Youtube Uploaded January 2023 - Irma Galuh Prameswari; Suroso, Eko (Universitas Cokroaminoto Palopo, 2026)
Slang is a language that is often used by Indonesian people, especially teenagers. Initially, the use of this language originated from the Betawi language which is often used in Indonesian television broadcasts such as films and soap operas. This research was conducted to find out about 1) Definition of slang, 2) Types of slang, 3) Factors for using slang, 4) Definition of YouTube content, 5) Types of YouTube content. In this study using a qualitative descriptive research method, namely obtaining information that is in accordance with the facts. The research data is slang on YouTube content Windah Basudara, a YouTube content creator who talks a lot about online games. The data collection technique in this study used listening and note-taking techniques. The listening technique was carried out after listening to and watching Windah Basudara's YouTube content to find out the form of slang spoken by the content creator. The note-taking technique is carried out after hearing what forms of slang are said by speakers. Basically this analysis was carried out with the intention of knowing the types of slang, types of slang, and factors of slang usage. The results of this research are the understanding of slang, the types of slang that exist in the content creator's utterances such as 1) slang personal pronouns, 2) slang shortening or beheading, 3) creative slang, 4) slang acronyms, 5) slang abbreviations, 6) absorption slang. And there is the use of slang itself due to social media, or electronic media, and environmental factors.